TATA KELOLA PERUSAHAAN DAN FAKTOR LAINNYA YANG MEMENGARUHI MANAJEMEN LABA - Azahra Dwi Rizqi; Anwar Harsono (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
The purpose of this research is to obtain empirical evidence about the factors which will affect on earnings management. The independent variables in this research are Institutional Ownership, Composition of Independent Commisioner, Size of the Board of Directors, Size of the Company, Audit Committee, Audit Quality, Leverage and Return on Asset. Dependent variable is Earnings Management. The research model that used in this research is multiple regression analysis. There are 69 companies that matched with this research criteria, which the population is manufacture companies are listed in Indonesian Stock Exchange during periode 2018 until 2020. The result of this research shows that Institutional Ownership, Composition of Independent Commisioner, Size of the Board of Directors, Size of the Company, Audit Committee and Leverage didn’t have any effect to earnings management. While Audit Quality and Return on Asset has significant effect on earnings management.